Protective role of chlorogenic acid on DNA damage caused by ochratoxin A exposure - Campra, Noelia Anahí (2020)
Chlorogenic acid (ChlA) has shown short-term protective effects against the cytogenotoxiceffects of ochratoxin A (OTA). The present study evaluated the effect of oraladministration of ChlA in male Wistar rats exposed to OTA. OTA (0.4 mg/kg bw/day), ChlA (5 mg/kg bw/day), or the combination of both, were administered orally toanimals during 28 days. No deaths, decrease in feed consumption or change in the bodyweight of animals were observed in any group. In the OTA-treated group a decrease inlocomotion as well as increased DNA damage in blood, kidney and bone marrow cellswere observed. ChlA alone was not genotoxic for animals. The combination of OTA+ChlA decreased the DNA damage by 37% in blood cells, by 55% in kidney cells andby 80% in bone marrow cells compared to OTA-treated group. In conclusion, oraltreatment with ChlA showed a good protective effect on genotoxicity produced byOTA in rats during 28 days exposure.